Glucose and collagen regulate human platelet activity through aldose reductase induction of thromboxane - Tang, Wai Ho (American Society for Clinical Investigation, 2011)
Diabetes mellitus is associated with platelet hyperactivity, which leads to increased morbidity and mortality from cardiovascular disease. This is coupled with enhanced levels of thromboxane (TX), an eicosanoid that facilitates platelet aggregation. Although intensely studied, the mechanism underlying the relationship among hyperglycemia, TX generation, and platelet hyperactivity remains unclear. We sought to identify key signaling components that connect high levels of glucose to TX generation and to examine their clinical relevance. In human platelets, aldose reductase synergistically modulated platelet response to both hyperglycemia and collagen exposure through a pathway involving ROS/PLCγ2/PKC/p38α MAPK. In clinical patients with platelet activation (deep vein thrombosis; saphenous vein graft occlusion after coronary bypass surgery), and particularly those with diabetes, urinary levels of a major enzymatic metabolite of TX (11-dehydro-TXB(2) [TX-M]) were substantially increased. Elevated TX-M persisted in diabetic patients taking low-dose aspirin (acetylsalicylic acid, ASA), suggesting that such patients may have underlying endothelial damage, collagen exposure, and thrombovascular disease. Thus, our study has identified multiple potential signaling targets for designing combination chemotherapies that could inhibit the synergistic activation of platelets by hyperglycemia and collagen exposure.